Learn how to prevent errors while writing Python-code (Texas Journal of Multidisciplinary Studies, 2022)
Python is widely used by many programmers around the world to create a variety of software applications. The most interesting thing about Python is that it is one of the most programmed languages compared to other programming languages with its simple code and extensive capabilities. That is, you do not have to declare the types of variables when creating a variable in python. It is selected automatically. In addition, error handling allows you to display and manage multiple errors of the same type. Incomplete parentheses and quotation marks in Python can cause various types of errors. Most programmers make mistakes during the coding process, and programmers detect some errors when Python executes a program. In the process of writing code, in some cases, Python detects an error and the program stops. In this case, we will look at the errors, and since there are many types of errors in Python, we will cover most of the errors in this article.